Negócios indiretos e negócios fiduciários - Lima, Marcelo Chiavassa de Mello Paula (2016)
Indirect act stricto sensu and fiduciary act are nothing new in the legal world (the origin is unknown, although it can be said that already the Romans knew), even if the doctrine just started to study them at the end of the 19th century. They are old business models that still are present, given its versatility to fulfill the legitimate interest of the parties. The institutes in question are a figure that for centuries remained outside of legal studies and that, even today, does not have much dogmatic deepening. Therefore, the aim of this master dissertation is to analyze both figures from a structural point of view, dogmatic and legal. In spite of they are figures that are derived from species hidden juridical act (Germany), abnormal (Spain) or indirect (Italy, Portugal, France and Brazil), along with simulation / fictitious interposition of person / business in circumvention of the law, from the point of legal view can not be considered the same thing. This is because the indirect act stricto sensu and fiduciary act reflect a valid legal business idea, unlike his brothers, who are characterized as invalid business. The external appearance is indeed similar - and therefore the link between the figures - to the extent that a part of the business is not necessarily externalized (from here the German naming hidden juridical act). To be able to better understanding of the subject and further discussion of the chosen argument, it is necessary to discuss the complex issue of contractual cause and its implication in these two negotiating figures (as an element that seeks to justify the economic operation carried out by the parties by economic function -individual) and the theory of typical and atypical juridical act, in order to allow further study concerning the structure of these two figures. The study and interpretation of foreign law is essential premise for attempting to structure these figures in Brazil, which is why it fall back on Italian law, Portuguese, German, Spanish, English, French and most countries belonging to the Spanish America to that, according to the problems encountered in these jurisdictions, trying to get the best deal on Brazilian law. The result will emerge the importance of these figures, and especially its wide acceptance in praxis both in Brazil and in other countries around the world. More than that, the conclusion will highlight the legality of these business models in the Brazilian and international law, as well as its increasing regulation as an important economic instrument at the disposal of private autonomy